2021
DOI: 10.3390/molecules26185483
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Useful Lipid Raft Model Membrane for Electrochemical and Surface Analytical Studies

Abstract: A model biomimetic system for the study of protein reconstitution or drug interactions should include lipid rafts in the mixed lipid monolayer, since they are usually the domains embedding membrane proteins and peptides. Four model lipid films composed of three components: 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), cholesterol (Chol) and sphingomyelin (SM) mixed in different molar ratios were proposed and investigated using surface pressure measurements and thermodynamic analysis of the monolayers at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…However, the overall expansion of the layer is a result of more fluid lipid film between more compact lipid domains with embedded protein in the lipid layer at the air–water interface. Moreover, the addition of the protein at a concentration of 0.02 mol % (vs lipids) causes a visible inflection in the isotherm at a surface pressure of 30 mN/m, which corresponds to the surface pressure value observed in real cell membranes. , This can also be visualized by the minimum in the C s –1 vs π plot (inset in Figure ), which is not observed in the isotherm recorded after spreading the empty liposomes and may result from the change in the organization of lipids in the presence of protein or from the changes in the HMG-CoA reductase conformation upon compression. , Thus, it can be concluded that some lipid–protein interactions occur at the physiological surface pressure of the membranes.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…However, the overall expansion of the layer is a result of more fluid lipid film between more compact lipid domains with embedded protein in the lipid layer at the air–water interface. Moreover, the addition of the protein at a concentration of 0.02 mol % (vs lipids) causes a visible inflection in the isotherm at a surface pressure of 30 mN/m, which corresponds to the surface pressure value observed in real cell membranes. , This can also be visualized by the minimum in the C s –1 vs π plot (inset in Figure ), which is not observed in the isotherm recorded after spreading the empty liposomes and may result from the change in the organization of lipids in the presence of protein or from the changes in the HMG-CoA reductase conformation upon compression. , Thus, it can be concluded that some lipid–protein interactions occur at the physiological surface pressure of the membranes.…”
Section: Resultsmentioning
confidence: 83%
“…The layer formed during the spreading of liposomes at the air−solution interface was significantly less stable (Figure 3B) than the 1:1:1 DOPC/Chol/SM monolayers formed from the mixture of lipids in chloroform/methanol on the PBS buffer subphase 35,36 or on the Tris-HCl buffer subphase. However, the proteoliposome-derived layers were more stable in time (light blue), and the surface pressure remained constant for many hours, as in the case of the monolayer formed by spreading the sample of the ternary mixture of lipids in the organic solvent (black) (Figure 3B).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this regard, lipid rafts are becoming promising therapeutic targets [1,[46][47][48][49][50][51]. Different approaches [6,[52][53][54][55] have contributed in the last two decades to unravel the biophysical, kinetic and mechanical properties of these membrane domains, including the use of: lipid raft model membranes (e.g. ternary lipid mixtures containing cholesterol, sphingomyelin and phosphatidylcholine derivatives in different molar ratios, to form liquid ordered phases, which may coexist with other rigid or fluid phases, depending on the temperature); giant unilamellar vesicles; giant plasma membrane vesicles and plasma membrane spheres; novel fluorescence lipid analogs; single-molecule imaging; and additional high temporal and spatial resolution techniques.…”
Section: Lipid Rafts As Mobile and Sorting Compartments In The Membra...mentioning
confidence: 99%